IMPLEMENTASI KEBIJAKAN REDISTRIBUSI TANAH OBYEK LANDREFORM DI DESA LALOMBI - Elfirawati, Elfirawati (Katalogis, 2016)
Land Redistribution activity of landreform Object is the division of the lands controlled by the State and have been affirmed to become the landreform object given to the peasants who havebeen qualified the Government Regulation No. 224 of 1961 which aims to improve the socio-economic situation of the people by organizing the fair and equitable distribution of land on people's livelihood of farmers in the form of land. So that the division can achievethe fair and equitable sharing. Based on this, the issues to be examined are the implementation of the Land Redistribution of landreform Object in the village Lalombi and the obstacles in the implementation of the Land Redistribution of landreform Object. The method used is qualitative.Data were collected through observation and interview. Research result is the implementation of Land Redistribution of landreform Object in the village Lalombi affected by four aspects, namely communication, resources, disposition and organizational structure. The implementation policy of Land Redistribution of Landreform has not been effective.Â There is still need for improvement in terms of resources and communication aspects. Communications aspect: Coordination between implementing activities object land redistribution of landreform is still not running properly, resulting in a miss communication that led to an untargeted implementation. Resources Aspect is still less effective in terms of human and infrastructure resources.